Consulting report - Lima Airport Partners - free trade zone in Jorge Chavez international airport - Coaguila Gonzales, Antonio Franco (Pontificia Universidad Católica del Perú, 2018)
The main objective of the present consulting report is to assess the opportunities and potential impact, considering advantages and challenges, of establishing a Free Trade zone in or around the area of the Jorge Chavez International Airport, in order to support Lima Airport Partners to prepare an initial study that will allow presenting the idea of the project to the Peruvian government. A thorough qualitative and quantitative analysis has been developed in order to identify which are the best practices and characteristics of success cases in Free Trade zones around airports and ports, as in the case of this project. Furthermore, this analysis has also allowed us to identify what is the current praxis in Peru and why the free trade zones do not perform adequately. These analyzes allowed the identification of four main enablers: (a) Legislation and Legal Framework, (b) Management Team, (c) Location and (d) Business Sectors, which were used as the basis for the proposal presented. On this sense, after the assessment it was decided that this Free Trade Zone has to focus on exports, specially taking advantage of the vast number of agricultural products produced in the central and northern region of the country. As well, the main characteristics under which the envisioned Free Trade Zone has to develop its activities have been identified as: (a) work under a single legislation, (b) be operated by a private entity, (c) be strategically located near the airport, port and highway, (d) include four major sectors: logistics, warehousing, manufacturing and trading. Moreover, prior implementing this proposal, it is important that the company has to have the full support of the government. Finally, the potential impact of the proposed Free Trade Zone has been assessed under three main expected outcomes: creation of jobs, increase in exports and further economic development; showing positive results that that support the general idea and objectives of the project.

El objetivo principal del presente informe de consultoría es evaluar las oportunidades y el posible impacto, considerando las ventajas y los desafíos, de establecer una zona franca en el área del Aeropuerto Internacional Jorge Chávez, con la finalidad de apoyar a Lima Airport Partners a preparar un estudio inicial que permitirá presentar la idea del proyecto al Gobierno Peruano. Se ha desarrollado un exhaustivo análisis cualitativo y cuantitativo para identificar cuáles son las mejores prácticas y características de casos de éxito en zonas francas alrededor de aeropuertos y puertos, como en el caso de este proyecto. Además, se ha podido identificar cómo es la práctica actual en Perú y por qué las zonas francas no funcionan adecuadamente. Estos análisis permitieron la identificación de cuatro habilitadores principales: (a) Legislación y Marco Legal, (b) Equipo de Gestión, (c) Ubicación y (d) Sectores Comerciales, que fueron utilizados como base para la propuesta presentada. En este sentido, luego de la evaluación se decidió que esta Zona Franca debe centrarse en las exportaciones, aprovechando especialmente la gran cantidad de productos agrícolas producidos en la región centro y norte del país. Asimismo, las principales características bajo las cuales la zona franca tiene que desarrollar sus actividades han sido identificadas como: (a) trabajar bajo una sola legislación, (b) ser operado por una entidad privada, (c) estar estratégicamente ubicado cerca del aeropuerto, puerto y carretera, (d) incluir cuatro sectores principales: logística, almacenamiento, fabricación y comercio. Además, antes de implementar esta propuesta, es importante que la compañía tenga el apoyo total del gobierno. Finalmente, el posible impacto de la zona franca propuesta se ha evaluado bajo tres principales resultados previstos: creación de puestos de trabajo, aumento de las exportaciones y mayor desarrollo económico; mostrando resultados positivos que apoyan la idea general y los objetivos del proyecto.
Keywords: Aeropuertos--Perú--Lima; Administración de empresas; https://purl.org/pe-repo/ocde/ford#5.02.04